2016
DOI: 10.1094/phyto-02-16-0114-r
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Spatiotemporal Dynamics of Oxytetracycline and Its Control Effect Against Citrus Huanglongbing via Trunk Injection

Abstract: Citrus huanglongbing (HLB) or greening is a devastating bacterial disease that has destroyed millions of trees and is associated with phloem-residing 'Candidatus Liberibacter asiaticus' (Las) in Florida. In this study, we evaluated the spatiotemporal dynamics of oxytetracycline in planta and its control effect against HLB via trunk injection. Las-infected 'Hamlin' sweet orange trees on 'Swingle' citrumelo rootstock at the early stage of decline were treated with oxytetracycline hydrochloride (OTC) using trunk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 40 publications
0
47
0
Order By: Relevance
“…Consequently, a proper wait time should be allowed between the application of antibiotics and harvest date (i.e., preharvest interval) in order to achieve low levels of antibiotics in harvested fruits. In fact, a recent study showed that trunk injection of oxytetracycline could result in low levels (202 µg/kg) of this antibiotic in citrus fruit [37]. The detected levels of oxytetracycline in citrus fruits were far below the minimum inhibitory concentration for gut flora, indicating negligible impacts on gut flora [37].…”
Section: Stability Of Oxytetracycline and Streptomycin In Citrus Seedmentioning
confidence: 96%
“…Consequently, a proper wait time should be allowed between the application of antibiotics and harvest date (i.e., preharvest interval) in order to achieve low levels of antibiotics in harvested fruits. In fact, a recent study showed that trunk injection of oxytetracycline could result in low levels (202 µg/kg) of this antibiotic in citrus fruit [37]. The detected levels of oxytetracycline in citrus fruits were far below the minimum inhibitory concentration for gut flora, indicating negligible impacts on gut flora [37].…”
Section: Stability Of Oxytetracycline and Streptomycin In Citrus Seedmentioning
confidence: 96%
“…are restricted to the phloem, which makes it difficult to effectively control them using foliar applications of bactericides. Among the alternatives that have been shown to overcome these limitations are trunk injection and the use of nanoemulsion formulations that enhance bactericide penetration [104,105].…”
Section: Perspectives For Disease Controlmentioning
confidence: 99%
“…Agricultural, urban, and natural tree stands have been the focus of extensive plant pathogen diagnostic and disease management research in recent decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] which recorded an increase in the number of new fungal and bacterial pathogens and their detrimental impact on agroecosystems, ecosystems, and the human society. The economic effects of these pathogens are reflected in lost fresh fruit produce [17][18][19], reduced yields and quality of fruit or wood and cork products [20,21], diminished ecological tree services, and death of whole trees, stands, and forest regions or decimation of fruit industries [19,22].…”
Section: Introductionmentioning
confidence: 99%
“…The most investigated tree fruit crops and their pathogens and insect pests are citrus (e.g. Candidatus Liberibacter asiaticus) [14,15], avocado (e.g. avocado thrips, Scirtothrips perseae; Phytophthora root rot, Phytophthora cinnamomi) [49,50], apple (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation